Evaluating the relative adsorption and biodegradation of 2-methylisoborneol and geosmin across granular activated carbon filter-adsorbers. (15th May 2022) - Yuan, Jie; Mortazavian, Soroosh; Crowe, Grace; Flick, Robert; Passeport, Elodie; Hofmann, Ron
Highlights: The biodegradative capacity of in-service GAC was identified. 14C-glucose respiration rate was an indicator of GAC biodegradative capacity. Potential MIB and geosmin biodegradation products were identified. Abstract: This study investigated the relative contributions of adsorption vs. biodegradation towards 2-methylisoborneol (MIB) and geosmin removal in the granular activated carbon (GAC) harvested from six filter-adsorbers in three drinking water treatment plants in the Great Lakes region. Column tests using azide-treated (sterilized) and untreated GAC in parallel were used to isolate the two effects. It was identified that substantial MIB and geosmin biodegradation in the GAC was occurring in one location, and that GAC in some cases had significant adsorption capacity after as much as 9 years of operation. Four alternative biological parameters (adenosine triphosphate, esterase activity, phosphatase activity, and 14 C-glucose respiration rate) were measured to quantify the biological activity of the GAC, and 14 C-glucose respiration rate was identified to be a potential indicator for GAC biodegradative capacity in terms of MIB, geosmin, and dissolved organic carbon. Several potential MIB and geosmin biodegradation products were also identified using non-targeted screening analysis. By using the new tools identified in this study, we can begin to better understand where adsorption vs. biodegradation may predominate under real-world conditions (e.g., different temperatures, influent concentrations, and empty bed contact time), leading ultimately to more cost-effective use of GAC. Graphical abstract: Image, graphical abstract